Scoring Systems for Estimating the Risk of Recurrent Venous Thromboembolism - Nichele, Ilaria; Tosetto, Alberto (Seminars in Thrombosis and Hemostasis, 2017)
The risk of recurrence after suspension of anticoagulant treatment in patients with a first episode of unprovoked venous thromboembolism (VTE) is highly variable from patient to patient. Not all patients are candidates for life-long anticoagulant therapy, essentially because there remain concerns for such an option regarding hemorrhagic complications and clinical monitoring. Thus, the “treat all” approach may be inadequate for some patients at low risk of relapse. Proper assessment of the recurrence risk may be helpful to decide the optimal therapeutic strategy in such patients. In recent years, attempts have been made to develop and validate clinical prediction rules to estimate the absolute risk of VTE recurrence in individual patients. This article highlights the advantages and disadvantages of such options, presenting three different prediction rules that have been published so far.
Keywords: venous thromboembolism; recurrence; clinical prediction rules; prognosis studies